Vård av kanin med gastrointestinal sjukdom - Karlberg, Lina (2010)
This work is intended primarily for animal nurses/veterinary technicians and describe parts of the rabbits digestive tract, causes of gastrointestinal disease, symptoms, diagnosis, general care of rabbits with gastrointestinal disease and how to prevent that gastrointestinal illness occur. The work is largely based on literature studies but also on a questionnaire sent out to rabbit owners to get answers on how they generally hold and care of rabbits, which gastrointestinal diseases that are most common, how owners care for their animals at home during illness and to examine if the owners think that the knowledge of this subject is good at his veterinarian/clinic.